Type 3c (pancreatogenic) diabetes mellitus secondary to chronic pancreatitis and pancreatic cancer. (November 2016) - Hart, Phil A; Bellin, Melena D; Andersen, Dana K; Bradley, David; Cruz-Monserrate, Zobeida; Forsmark, Christopher E; Goodarzi, Mark O; Habtezion, Aida; Korc, Murray; Kudva, Yogish C; Pandol, Stephen J; Yadav, Dhiraj; et al.
Summary: Diabetes mellitus is a group of diseases defined by persistent hyperglycaemia. Type 2 diabetes, the most prevalent form, is characterised initially by impaired insulin sensitivity and subsequently by an inadequate compensatory insulin response. Diabetes can also develop as a direct consequence of other diseases, including diseases of the exocrine pancreas. Historically, diabetes due to diseases of the exocrine pancreas was described as pancreatogenic or pancreatogenous diabetes mellitus, but recent literature refers to it as type 3c diabetes. It is important to note that type 3c diabetes is not a single entity; it occurs because of a variety of exocrine pancreatic diseases with varying mechanisms of hyperglycaemia. The most commonly identified causes of type 3c diabetes are chronic pancreatitis, pancreatic ductal adenocarcinoma, haemochromatosis, cystic fibrosis, and previous pancreatic surgery. In this Review, we discuss the epidemiology, pathogenesis, and clinical relevance of type 3c diabetes secondary to chronic pancreatitis and pancreatic ductal adenocarcinoma, and highlight several important knowledge gaps.